(untitled) (European Journal of Pure and Applied Mathematics, 2024)
A new type of algebraic structure, called a quasi generalized exchange algebra(qGE-algebra), with the GE-algebra conditions is introduced and its properties are investigated. The concepts of qGE-subalgebra, qGE-filter, closed qGE-filter and strong qGE-filter of a quasi GE-algebra are introduced and their relationships are discussed. The conditions for a subset of a quasi GE-algebra to be a qGE-filter are given.